Clinical guidelines for maxillary sinus floor elevation with sinus membrane lesions - RONG Mingdeng (口腔疾病防治, 2020)
Maxillary sinus membrane lesions have been broadly detected before implant surgery in the posterior maxilla region, resulting in uncertainty regarding maxillary sinus floor elevation surgery. In this context, we composed this commentary article based on the current literature and the clinical experience of our department. We discuss the common lesion types shown by CBCT including membrane pathological thickening, polyps/cystic lesions and air-liquid level in the sinus. Maxillary sinus floor elevation surgery can be conducted in patients with membrane thickening of 2-5 mm or with polyps/cysts of less than half of the sinus height (because the above symptoms have little influence on the outcome of surgery). Membrane thickening of more than 5 mm with ostium obstruction, antrochoanalpolyps, mucoceles and cysts of more than half of the sinus height should be carefully treated. Different treatments can be performed such as conducting elevation surgery while retaining the cyst, removing the cyst before surgery or removing the cyst during surgery based on the cyst type and size, inflammation, patency of the ostium, etc. Antibiotics-anti-inflammatory-aspiration, surgical debridement and oral lesions eliminations are generally used for treating post-operative sinusitis. Presurgical radiographic evaluation is the key to diagnosing and treating these membrane lesions. We highly advocate collaboration between our dentists and otolaryngologists on this issue.